2021
DOI: 10.1002/adem.202101156
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Quasistatic Compression Performance of Arch Microstrut Lattice Structure by Selective Laser Melting

Abstract: In recent years, lattice structures have been widely used in aerospace, automobile, biomedicine, and other fields. Lattice structures are porous structures composed of repeating cellular units. Because of their high-porosity spatial structure and low density, lattice structures have high specific strength, high specific stiffness, good energy absorption ability, excellent thermal and acoustic insulation properties, and so on. [1][2][3][4][5][6] The properties of the lattice structures are defined by the cell s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 32 publications
(38 reference statements)
0
9
0
Order By: Relevance
“…According to the analysis of finite element simulations, it was found that the novel hexagonal prism TLM had excellent energy absorption capacity. The impact resistance and energy absorption properties were measured using two important indicators: specific energy absorption (SEA) and ideal energy absorption efficiency [24,25]. The energy absorbed per unit mass was defined as SEA, which could be expressed as follows: Where s was the stress of the hexagonal prism TLM's meso-structures, e was the strain of the structures, r* was the relative density of the structures, and r was the density of the A1Si10Mg alloy.…”
Section: Energy Absorption Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…According to the analysis of finite element simulations, it was found that the novel hexagonal prism TLM had excellent energy absorption capacity. The impact resistance and energy absorption properties were measured using two important indicators: specific energy absorption (SEA) and ideal energy absorption efficiency [24,25]. The energy absorbed per unit mass was defined as SEA, which could be expressed as follows: Where s was the stress of the hexagonal prism TLM's meso-structures, e was the strain of the structures, r* was the relative density of the structures, and r was the density of the A1Si10Mg alloy.…”
Section: Energy Absorption Analysismentioning
confidence: 99%
“…Zhang et al [23] designed enhanced pyramidal TLM through node optimization design. Ding and Yao et al [24,25] fabricated ARCH TLM by optimizing the center line of BCC strut. Wang et al [13] modified the traditional FCC TLM by adding a cross-rod at the center of its RVU.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [20] designed enhanced pyramidal unit cell through node optimization design. Ding and Yao et al [21,22] fabricated ARCH unit cell by optimizing the center line of BCC strut. Wang et al [12] modi ed the traditional FCC TLM by adding a cross-rod at the center of the unit cell.…”
Section: Introductionmentioning
confidence: 99%
“…[20] At the design stage, difficulties include the choice of the unit cell and its repetition in order to fill a defined design space while obtaining a computer-aided design (CAD) model that can be easily handled and modified. [21] New approaches are proposing the adoption of neural networks that allow tuning the desired mechanical response in much shorter computational times. [22] Simulation is addressed in many studies today [10,18,[23][24][25] with a special attention to the development of plastic and damage models.…”
Section: Introductionmentioning
confidence: 99%
“…[26] Particularly in the automotive field, PBF-LB/M of aluminum alloys is certainly the most promising solution and cubic unit cells are widely adopted owing to the relative ease of design and modeling. [15,21,27] In spite of that, PBF-LB/M processes are not totally free from manufacturing boundaries, the major ones being the minimum size of features that can be built and the maximum overhang length. [27,28] The ASTM standard "Additive manufacturing -Design -Part 1: Laser-based powder bed fusion of metals" provides insightful definitions of the minimum size of features such as gaps, holes, channels, walls, and beams, as a function of the width of the melt pool.…”
Section: Introductionmentioning
confidence: 99%